Instilling The Value of Tolerance In Generation Z Through Islamic Education in The Social Media Era - Masrufah, Masrufah (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
Generation Z, as digital natives, are highly exposed to the dynamics of social media, which can shape both positive and negative attitudes, particularly regarding religious tolerance. This study aims to analyze the role of Islamic education in instilling the value of tolerance among Generation Z by utilizing social media as a medium for non-formal learning. The method used is library research with a descriptive-analytical approach, examining relevant academic literature such as journals, books, and reports. The findings indicate that tolerance values derived from the Qur’an and Hadith can be integrated into Islamic education in ways that resonate with the digital lifestyle of Generation Z. Furthermore, Islamic education, through formal, non-formal, and social media-based approaches, is effective in cultivating tolerant, moderate, and inclusive attitudes among the younger generation. This study emphasizes that social media should not only be viewed as a challenge but also as a potential platform for nurturing tolerance and global harmony.